The Principle of Judicial Independence in the Scope of the Practice of the Court of Justice of the European Union and the European Court of Human Rights: the Experience of Poland - Mits, Anastasiia (Problems of legality, 2026)
This article examines the principle of judicial independence through the lens of the case law of the Court of Justice of the European Union and the European Court of Human Rights, using the judicial reforms in the Republic of Poland as a case study. The aim of the research is to identify and systematise the differences in the approaches adopted by the European courts in assessing violations of judicial independence, as well as to analyse the methods of legal interpretation applied in the relevant judgments. The study provides a detailed review of the texts of key judgments of the Court of Justice of the European Union and the European Court of Human Rights concerning judicial appointments, guarantees of judicial independence, institutional autonomy of judicial bodies, and the right to effective judicial protection. It demonstrates that the CJEU focuses primarily on the functional dimension of judicial independence in the context of the application of European Union law and compliance with the requirements of Article 19(1) TEU, whereas the ECtHR adopts a broader, systemic approach by assessing judicial independence as an integral element of the right to a fair trial under Article 6 of the European Convention on Human Rights. Particular attention is paid to differences in the standard of review, the depth of institutional analysis, and the role of the national constitutional context in the case law of both courts. The article argues that these divergences lead to different legal consequences for the Member State concerned and affect the effectiveness of the protection of judicial independence at the European level. It is concluded that a comparative analysis of the case law of the CJEU and the ECtHR not only allows for a deeper understanding of the nature of contemporary threats to judicial independence, but also reveals both the limits and the potential of European mechanisms for safeguarding the rule of law in the context of constitutional transformations within Member States.